Perlindungan Konsumen Terhadap Liquid Tanpa Tanggal Kadaluarsa dalam Perspektif Hukum Islam (Studi Kasus Toko Vape Parepare) - Putri Anisa (Program Studi Hukum Ekonomi Syariah, Institut Agama Islam Negeri Parepare, 2024)
This thesis examines consumer protection against the sale and purchase of liquids that do not include an expiration date according to the perspective of Islamic law (Case study at the Star Vape Shop in Parepare City). There are three main problems studied in this study, namely 1) how is the practice of buying and selling liquids at the Star Vape Shop, 2) how is consumer protection against buying and selling that does not include an expiration date 3) how is the Islamic law review of buying and selling liquids that do not include an expiration date.This research is a field research with a case study. To overcome the problems analyzed, primary data was obtained through observation, interviews, and documentation. Meanwhile, secondary data used include literature, books, journals, and relevant laws related to consumer protection.The results of this study indicate that (1) the Star Vape Shop sells liquids without an expiration date listed, but the shop provides information that the liquid expiration information can be seen from the liquid excise itself, the liquid expiration is said to be a maximum of 3 years from the issuance of excise. (2) Star Vape Store provides various rights and obligations in consumer protection to its consumers while making purchases. (3) When the legal status of electronic cigarettes is equated with conventional cigarettes, consuming vape is said to be between makruh and haram, depending on the level of benefits and harms.